2018
DOI: 10.3171/2016.9.jns161710
|View full text |Cite
|
Sign up to set email alerts
|

De novo AVM formation following venous sinus thrombosis and prior AVM resection in adults: report of 2 cases

Abstract: Brain arteriovenous malformations (AVMs) are traditionally considered congenital lesions, arising from aberrant vascular development during the intrauterine period. Rarely, however, AVMs develop in the postnatal period. Individual case reports of de novo AVM formation in both pediatric and adult patients have challenged the traditional dogma of a congenital origin. Instead, for these cases, a dynamic picture is emerging of AVM growth and development, initially triggered by ischemic and/or traumatic events, cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…27 Case reports have been documented since. 13,633 The findings support the concept that the process of AVM formation is multifactorial and is related to congenital, environmental and haemodynamic factors. 2,5 De novo AVM risk factors noted included a history of haemorrhage, ischaemic stroke, radiation exposure, familial AVMs and aneurysm, dural arteriovenous fistula, Moyamoya disease or cavernoma on initial diagnosis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…27 Case reports have been documented since. 13,633 The findings support the concept that the process of AVM formation is multifactorial and is related to congenital, environmental and haemodynamic factors. 2,5 De novo AVM risk factors noted included a history of haemorrhage, ischaemic stroke, radiation exposure, familial AVMs and aneurysm, dural arteriovenous fistula, Moyamoya disease or cavernoma on initial diagnosis.…”
Section: Discussionsupporting
confidence: 78%
“…2,5 De novo AVM risk factors noted included a history of haemorrhage, ischaemic stroke, radiation exposure, familial AVMs and aneurysm, dural arteriovenous fistula, Moyamoya disease or cavernoma on initial diagnosis. 13,633…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of other angiogenetic factors such as KRAS mutations [27], phosphorylated extracellular signal-regulated kinase (pERK) and CD105 (endoglin) [28] has also been reported. De novo bAVM formation after venous sinus thrombosis has also been observed, with impaired venous outflow leading to congestion, parenchymal ischaemia and hypoxia and increased angiogenesis as the proposed mechanism [29].…”
Section: Discussionmentioning
confidence: 99%
“…3,7,19,21,22,24,29,30 Shi et al and Pabaney et al suggested that AVM development in adult patients may be "triggered by ischemic and/or traumatic events." 27,29 The number of de novo AVMs in adults is consequently so low that it does not affect the conclusions made in this study. Hence, we must conclude that the assumption of an annual hemorrhage risk that decreases after becoming symptomatic very likely is incorrect.…”
Section: Discussionmentioning
confidence: 99%